2019
DOI: 10.1109/access.2019.2941560
|View full text |Cite
|
Sign up to set email alerts
|

R-PEKS: RBAC Enabled PEKS for Secure Access of Cloud Data

Abstract: In the recent past, few works have been done by combining attribute-based access control with multi-user PEKS, i.e., public key encryption with keyword search. Such attribute enabled searchable encryption is most suitable for applications where the changing of privileges is done once in a while. However, to date, no efficient and secure scheme is available in the literature that is suitable for these applications where changing privileges are done frequently. In this paper our contributions are twofold. Firstl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…To date, there is no user-level role recommendation model for the RBAC system to optimize the UA, dynamically based on the requirements. Further, in R-PEKS [17], it is proposed in a future work that there is need to optimize the UA for better performance and security in dynamic user-permission assignments.…”
Section: Role Mining Methodsmentioning
confidence: 99%
“…To date, there is no user-level role recommendation model for the RBAC system to optimize the UA, dynamically based on the requirements. Further, in R-PEKS [17], it is proposed in a future work that there is need to optimize the UA for better performance and security in dynamic user-permission assignments.…”
Section: Role Mining Methodsmentioning
confidence: 99%
“…Simulation experiments showed that this proposed approach could make decisions based on both tasks and roles with a latency of less than 0.25 s, which was commercially viable. In [ 12 ], Rao et al creatively introduced RBAC to multi-user PEKS, where any group of users can connect to the server to search and access encrypted files based on their roles. The proposed approach could protect IoT data resources from both authority and confidentiality perspectives, and experiments showed that role-based PEKS improved efficiency by 90% compared with ordinary multi-user PEKS.…”
Section: Related Workmentioning
confidence: 99%
“…There are many other forms of data resource security protection techniques in IoT, such as firewall, authentication, encryption, intrusion detection system (IDS), etc. In [ 12 ], Rao et al used PEKS and AES to encrypt the data resources of the device. In [ 17 ], Wang et al used cryptography to ensure the privacy of data on the chain.…”
Section: Related Workmentioning
confidence: 99%
“…RBAC is a security mechanism that allows users to access data based on their roles within an organisation [39]. The authors in [40] introduced RBAC to PEKS using free bilinear, as bilinears have high computational cost. The authors used the RBAC mechanism to simplify the frequent user's permission assignment within a large organisation.…”
Section: Searchable Encryption Searchable Encryption (Se) Is Amentioning
confidence: 99%